Protection and diagnostic interference induced by heat-inactivated, phage-inactivated and live vaccine prototypes against animal tuberculosis - Fernández-Veiga, Leire; Fuertes, Miguel; Geijo, María V.; Elguezabal, Natalia; Serrano-Mestre, Jose L.; Vázquez-Iniesta, Lucía; Prados-Rosales, Rafael; Michelet, Lorraine; Boschiroli, Maria Laura; Pérez de Val, Bernat; Jones, Gareth J.; Juste, Ramón A.; et al. (Frontiers in Veterinary Science, 2025)
IntroductionVaccination emerges as a promising cost-effective tool to reduce the impact and spread of animal tuberculosis, especially in regions where test-and-slaughter eradication strategy is socioeconomically unfeasible or unfruitful for different reasons, provided it is safe, efficacious and compatible with diagnosis.MethodsIn this study, we preliminarily evaluated the diagnostic interference (using guinea pigs) and the protective efficacy (using mice) of three heat-inactivated, three phage-inactivated and one live attenuated vaccine prototypes prepared from M. bovis, M. caprae, and M. microti.Results and discussionPhage-inactivation killed almost all (96.41–99.92%) bacteria to be included in vaccines and filtering was used to remove the remaining viable cells. All the assayed vaccines induced skin test reactions in response to bovine tuberculin, but they were smaller in the phage-inactivated vaccine groups. All the vaccines were diagnosis-compatible with defined skin test antigens based on ESAT-6, CFP-10, and Rv3615c. In contrast with the rest of prototypes, vaccination with heat- and phage-inactivated M. microti did not prompt the production of detectable anti-MPB70+MPB83 antibodies. Mean bacterial burden was lower in all vaccinated groups in comparison with the control, being significantly reduced in the lungs of the heat-inactivated M. microti and M. caprae and phage-inactivated M. caprae groups. Considering both diagnostic interference and protection collectively, the heat-inactivated M. microti vaccine showed the best performance. Further studies to evaluate these vaccines and to improve phage-driven inactivation are warranted.